Novel Double-Mode O-Type Source of Coherent Subterahertz Radiation - Odarenko, E. N.; Shmat'ko, A. A.; Yudintcev, P. V.; Vasilenko, V. M. (IEEE, 2010)
A new type of subterahertz generator at harmonics of BWO oscillations in the mode of diffraction radiation is proposed. The nonlinear multidimensional theory of the double-mode beam-wave interaction at the harmonics of the BWO is developed. The regions of problem parameters values, corresponding to diffraction radiation excitation are defined.
Keywords: double mode O-type electron device; subterahertz radiatioin; diffraction radiation